MINI REVIEW: SINTESIS DAN KARAKTERISASI NANOPARTIKEL ALUMINIUM OKSIDA (Al2O3) DENGAN METODE PRESIPITASI - Sari, Nadia Fellinda Wanda; Hiyahara, Irfan Ashari (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2025)
This review article aims to compare and analyze the latest research on the synthesis and characterization of aluminum oxide nanoparticles from inorganic waste. Aluminum Oxide (Alumina, Al2O3) is a compound formed from aluminum and oxygen. The nature of Al2O3 is resistant to corrosion. Based on a literature review, the synthesis of aluminum oxide nanoparticles can be synthesized by precipitation methods, sol-gel methods, electrolysis methods, green synthesis methods, sonochemical methods and others. The precipitation method is a method used to produce a powder that has advantages including homogeneous mixing that occurs from a reactant precipitate reduces the reaction temperature and the process of this method to synthesize metal oxide powder is very simple. This method has several disadvantages such as not being able to run well when using reactants that have different solubilities, this process is not appropriate for the manufacture of materials with a high level of purity, in addition this method does not have common synthesis conditions in the formation of several metal oxides. In this review, we will discuss the synthesis of Al2O3 nanoparticles characterization results using X-Ray Diffraction (XRD), Scanning Electron Microscope (SEM). Therefore, this mini review reviews the development of Al2O3 characterization synthesis with precipitation method. Keywords : Synthesis, Al2O3, nanoparticles, Precipitation